2015
DOI: 10.1111/trf.13397
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors influencing ferritin levels in 14,126 blood donors: results from the Danish Blood Donor Study

Abstract: Genetic variants associated with hemochromatosis may protect donors against depleted iron stores. In addition, we showed that presence of the T-allele at rs855791 in TMPRSS6 was associated with lower iron stores in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
4
25
0
Order By: Relevance
“…Nevertheless, the frequency of the A736V was similar in first‐time and high‐intensity groups, and it had no observed association with hemoglobin or ferritin within high‐intensity donors in longitudinal models. The variable effects of A736V among first‐time and high‐intensity donors may explain why it did not impact ferritin in women in a large cohort of donors with a range of donation intensity and is consistent with its variable association with hemoglobin and ferritin found in other studies …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, the frequency of the A736V was similar in first‐time and high‐intensity groups, and it had no observed association with hemoglobin or ferritin within high‐intensity donors in longitudinal models. The variable effects of A736V among first‐time and high‐intensity donors may explain why it did not impact ferritin in women in a large cohort of donors with a range of donation intensity and is consistent with its variable association with hemoglobin and ferritin found in other studies …”
Section: Discussionsupporting
confidence: 88%
“…11,12 There is evidence for higher hemoglobin or ferritin in blood donors with H63D and C282Y, but the findings sometimes vary by sex and number of mutated alleles. [8][9][10]12 Here, we found that H63D was more strongly associated with increased ferritin and hemoglobin in high-intensity donors than C282Y. This was somewhat surprising, since C282Y is more strongly associated with hemochromatosis.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Studies of blood donors have strengthened the hypothesis that genetic variants of iron genes, especially TMPRSS6 and HFE, reported to influence iron parameters 49,50 and hepcidin, 51 may predispose to or protect individuals from iron deficiency. 52 In a novel murine model, genetic iron deficiency anemia was caused by loss of the enzyme of the sulfur assimilation pathway bisphosphate-39-nucleotidase (Bpnt1). Iron deficiency anemia characterizes both germinal and intestinal conditional Bpnt1 knockout mice, establishing a novel link between sulfur and iron homeostasis.…”
Section: Genetics Of Iron Deficiencymentioning
confidence: 99%
“…The Danish Donor Cohort recently added specific consent for collection, retention, and testing of DNA and plasma samples from a subset of blood donors in Denmark. 27 This study is in the process of generating GWAS and other laboratory data to allow analyses of donor genetic and biological factors that may impact downstream donor health and transfusion efficacy and complications. However, they have not acquired and stored samples of RBCs for evaluation of storage hemolysis parameters.…”
Section: Discussionmentioning
confidence: 99%